De la Liga Racionalista a cómo educa el Estado a tu hijo: el itinerario de Julio Barcos - Pita González, Alexandra (2012)
This article focuses on the anarchist journey Julio Barcos. The Argentine intellectual itinerary is developed in three stages, corresponding to the rationalist education project spread in some periodicals (Popular School, Bulletin of the League Rationalist and Popular Library), the Central American experience in founding the Quasimodo magazine and the publication of his book How to Educate your child the State (1927). Specifically, we study the speeches related to these political-educational proposals which involved boats, to understand the changes and continuities that can be seen in representations relating to education as well as to key stakeholders: teachers, students and the state.